2022
DOI: 10.1097/sla.0000000000005537
|View full text |Cite
|
Sign up to set email alerts
|

No Reduction in Parastomal Hernia Rate 3 Years After Stoma Construction With Prophylactic Mesh

Abstract: Objective: The primary objective was to compare rates of parastomal hernia (PSH) 3 years after stoma construction with prophylactic mesh or no mesh. A secondary objective was to compare complications requiring reintervention within 3 years. Background: Recent studies have shown that a prophylactic mesh does not reduce the rate of PSH contrary to older studies. Long-term data on efficacy and safety is however scarce. Methods: A randomized controlled double-blind multicenter trial. Patients planned for permanent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
(73 reference statements)
0
9
0
Order By: Relevance
“…12 Other studies report similar figures, with rates ranging from 2 to 28% for ileostomies and 0 to 48% for colostomies. [29][30][31][32][33][34][35][36] In general, loop stomas-especially loop colostomies-have a higher rate of parastomal hernia formation than end stomas, almost certainly due to size of the fascial defect needed to bring both ends of the intestine through the abdominal wall. Although there is no widely accepted criteria for sizing the fascial defect, most colorectal surgeons recommend keeping the opening as small as possible while still allowing the easy passage of the tip of a finger alongside the intestine since larger openings are associated with higher rates of parastomal hernia.…”
Section: Late Complications Parastomal Herniamentioning
confidence: 99%
See 1 more Smart Citation
“…12 Other studies report similar figures, with rates ranging from 2 to 28% for ileostomies and 0 to 48% for colostomies. [29][30][31][32][33][34][35][36] In general, loop stomas-especially loop colostomies-have a higher rate of parastomal hernia formation than end stomas, almost certainly due to size of the fascial defect needed to bring both ends of the intestine through the abdominal wall. Although there is no widely accepted criteria for sizing the fascial defect, most colorectal surgeons recommend keeping the opening as small as possible while still allowing the easy passage of the tip of a finger alongside the intestine since larger openings are associated with higher rates of parastomal hernia.…”
Section: Late Complications Parastomal Herniamentioning
confidence: 99%
“…36 Similar findings were recently reported from the GRECCAR 7 trial involving 200 patients at 18 hospitals in France (31 vs. 28% at 2 years after surgery, p ¼ 0.77) 58 and the STOMAMESH trial involving 240 patients at 8 hospitals in Sweden (39 vs. 37% at 3 years after surgery, p ¼ 0.83). 35,59 Interestingly, no major study found higher rates of perioperative complications associated with mesh implantation, including surgical site infections. Rates of prophylactic mesh placement during ostomy formation do not appear to have increased dramatically, at least in the United States, suggesting that the decision to place or not to place mesh remains individualized.…”
Section: Late Complications Parastomal Herniamentioning
confidence: 99%
“…The su cient treatment and prevention of a parastomal hernia is important because this health condition frequently occurs when creating an end colostomy, theincidence occuring up to 64% [1][2][3]. In order to reduce these incidence, prophylactic mesh placement (PMP) has been studied in several randomized clinical trials [4,5]. A reduced rate of parastomal hernias was detected in the majority of the studies [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In order to reduce these incidence, prophylactic mesh placement (PMP) has been studied in several randomized clinical trials [4,5]. A reduced rate of parastomal hernias was detected in the majority of the studies [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that an important drawback in the interpretation of the past and recent evidence may be related to the short follow-up of RCTs published so far [ 11 , 12 ], with a prolonged follow-up in only four studies [ 13 16 ]. On the other hand, a further difficulty in the interpretation of findings is the use of different surgical techniques for mesh placement, with the most frequent being a retromuscular position using an open approach (laparotomy) or an intraperitoneal position using a laparoscopic approach (keyhole or modified Sugarbaker) [ 5 , 12 ].…”
Section: Introductionmentioning
confidence: 99%